Comparison of decision rules to mediate negotiations with incomplete information - Sarabando, Paula (2015)
Decisions in society resulting from negotiation among two parties are often inefficient (in terms of Pareto efficiency) as the parties fail to identify an agreement that would make both better off. A third party mediating the negotiation can increase the chances of reaching a Pareto efficient alternative. However, in most practical situations the mediator does not have a precise model of the parties’ preferences, and therefore cannot identify which alternatives are efficient. This paper assesses the performance of decision rules that a mediator can apply in multi-issue bilateral negotiation analysis given ordinal information about the importance of the issues and the value of the potential alternatives in each issue. We assume the preferences of the parties can be modelled by an additive multiattribute value function, but without assuming the precise parameters of this model are known. We study three mediation criteria: maximising the sum of the values, maximising the product of the excesses, or maximising the minimal proportion of potential. Monte-Carlo simulation is used to assess how good the alternative chosen by each decision rule is, and to provide guidelines about the use of these rules in a context of selecting a subset of promising alternatives.